1946
DOI: 10.1021/ie50435a027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing Rate on Vegetables

Abstract: VIuch confusion appears in the literature concerning the effects of fast and slow freezing on the quality of vegetables. In this study, five different rates of freezing were employed, ranging from very rapid, by means of liquid air, to very slow, in an insulated box. Peas and snap beans were blanched, frozen, and stored at -6°F. for six months. Analyses were made for ascorbic acid, carotene, and thiamine.Riboflavin was run on peas only. Analyses were madfe on raw, blanched, and frozen samples, and again after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1952
1952
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…The vitamin data in Table 11.10 are in reasonably good agreement with other comparable studies dealing with cooking losses of (3-carotene in peas and green beans (Lee et al 1946), thiamin in green peas (Barnes and Tressler 1943;Lee et al 1946;Martin et al 1960), and riboflavin in green beans (Lee et al 1946;Phillips and Fenton 1945;Van Duyne et al 1950). Lee et al (1946) reported that riboflavin losses during cooking of frozen green peas range from 0 to 39%, which is contrary to the results in Table 11.10.…”
Section: Loss Of Nutrients During Cooking Of Previously Frozen Vegetasupporting
confidence: 86%
See 2 more Smart Citations
“…The vitamin data in Table 11.10 are in reasonably good agreement with other comparable studies dealing with cooking losses of (3-carotene in peas and green beans (Lee et al 1946), thiamin in green peas (Barnes and Tressler 1943;Lee et al 1946;Martin et al 1960), and riboflavin in green beans (Lee et al 1946;Phillips and Fenton 1945;Van Duyne et al 1950). Lee et al (1946) reported that riboflavin losses during cooking of frozen green peas range from 0 to 39%, which is contrary to the results in Table 11.10.…”
Section: Loss Of Nutrients During Cooking Of Previously Frozen Vegetasupporting
confidence: 86%
“…Lee et al (1946) reported that riboflavin losses during cooking of frozen green peas range from 0 to 39%, which is contrary to the results in Table 11.10. Studies by Dawson et al (1949), Lee et al (1946),…”
Section: Loss Of Nutrients During Cooking Of Previously Frozen Vegetamentioning
confidence: 57%
See 1 more Smart Citation
“…This result was noted in the preliminary observations made by Joslyn & Marsh (68). Lee et al (64) reported no difference in texture, microscopic ap pearance, or palatability in strawberries, raspberries, and sliced peaches packed in sirup whether frozen very slowly, very rapidly, or at intermediate rates.…”
Section: Ice Formation and Its Effect On Structurementioning
confidence: 98%
“…MacArthur (60,61) agreed with him that slow freezing re sulted in more tissue destruction by large, internal ice crystals than more rapid freezing, particularly in asparagus. Lee et al (62) found that although slow freezing resulted in the formation of large veins of ice in peas and snap beans, no injury was evident when the product was thawed and no signifi cant differences in palatability could be detected between produds frozen slowly and those frozen rapidly. Similarly, the rate of freezing had no effect on the palatability of spinach, corn, and lima beans although with aspara gus, differences in texture were found with different rates of freezing (63).…”
Section: Ice Formation and Its Effect On Structurementioning
confidence: 99%